Asymptotic properties of M-estimates of parameters in a nonlinear regression model with discrete time and singular spectrum - Ivanov, O. V.; Orlovs’kyi, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study a nonlinear regression model with discrete time and observations errors whose spectrum is singular. Sufficient conditions are obtained for the consistency, asymptotic uniqueness and asymptotic normality of the M-estimates of the unknown parameters.